Determinants of currency choice in cross-border bank loans - Lorenz Emter; Peter McQuade; Swapan-Kumar Pradhan; Martin Schmitz (European Central Bank (ECB), 2024)
This paper provides insights into the determinants of currency choice in cross-border bank lending, such as bilateral distance, financial and trade linkages to issuer countries of major currencies, and invoicing currency patterns. Cross-border bank lending in US dollars, and particularly in euro, is highly concentrated in a small number of countries. The UK is central in the international network of loans denominated in euro, although there are tentative signs that this role has diminished for lending to non-banks since Brexit. Offshore financial centres are pivotal for US dollars loans, reflecting, in particular, lending to non-bank financial intermediaries in the Cayman Islands, possibly as a result of regulatory and tax optimisation strategies. The empirical analysis suggests that euro-denominated loans face the "tyranny of distance", in line with predictions of gravity models of trade, in contrast to US dollar loans. Complementarities between trade invoicing and bank lending are found for both the euro and the US dollar.
Keywords: F31; F33; F34; F36; G21; 330; dominant currency paradigm; currency denomination; cross-border banking; gravity